A core–shell TiO2@C nano-architecture: facile synthesis, enhanced visible photocatalytic performance and electrochemical capacitance1. Issue 77 (22nd August 2015) - Hou, Linrui; Hua, Hui; Cao, Hui; Zhu, Siqi; Yuan, Changzhou
<x xml:space="preserve">Abstract</x> A mesoporous core–shell TiO2@C nanohybrid exhibited remarkable photocatalytic degradation efficiency and stability for methylene blue under visible light irradiation, and attractive electrochemical behaviors for electrochemical capacitors.